Honeybee locomotion is impaired by Am-Ca(V)3 low voltage-activated Ca(2+) channel antagonist - Rousset, M. (Sci Rep, 2017)
Voltage‐gated Ca(2+) channels are key transducers of cellular excitability and participate in several crucial physiological responses. In vertebrates, 10 Ca(2+) channel genes, grouped in 3 families (Ca(V)1, Ca(V)2 and Ca(V)3), have been described and characterized. Insects possess only one member of each family. These genes have been isolated in a limited number of species and very few have been characterized although, in addition to their crucial role, they may represent a collateral target for neurotoxic insecticides. We have isolated the 3 genes coding for the 3 Ca(2+) channels expressed in Apis mellifera. This work provides the first detailed characterization of the honeybee T-type Ca(V)3 Ca(2+) channel and demonstrates the low toxicity of inhibiting this channel. Comparing Ca(2+) currents recorded in bee neurons and myocytes with Ca(2+) currents recorded in Xenopus oocytes expressing the honeybee Ca(V)3 gene suggests native expression in bee muscle cells only. High‐voltage activated Ca(2+) channels could be recorded in the somata of different cultured bee neurons. These functional data were confirmed by in situ hybridization, immunolocalization and in vivo analysis of the effects of a Ca(V)3 inhibitor. The biophysical and pharmacological characterization and the tissue distribution of Ca(V)3 suggest a role in honeybee muscle function.